Rock guitar for dummies - Chappell, Jon (--For dummies, 2001)
A guide to playing rock guitar that includes information on power cords and rhythm figures, improvising solos, playing lead guitar, exploring the mechanics of guitars, amps, and effects, and caring for guitars; includes a CD with lead guitar riffs and rhythm guitar styles.